A high‐drug‐loading self‐assembled nanoemulsion enhances the oral absorption of probucol in rats. Issue 4 (1st February 2013) - Zhang, Zhiwen; Huang, Jian; Jiang, Shijun; Liu, Zeying; Gu, Wangwen; Yu, Haijun; Li, Yaping
Abstract The purpose of this study was to develop a high‐drug‐loading nanoemulsion by self‐assembly to improve the oral absorption of high dosing poorly water‐soluble drugs. Probucol was selected as a model drug and the probucol‐loaded self‐assembled nanoemulsion (PSN) was prepared and characterized. Moreover, the intestinal absorption and in vivo pharmacokinetic behavior of PSN were evaluated in rats after oral administration. The experimental results indicated that PSN was nanometer‐sized droplets with the mean diameter of 40.32 ± 0.31 nm and polydispersity index of 0.184 ± 0.005. The aqueous solubility of probucol was remarkably increased after its incorporation into PSN. Compared with free drug suspension, the intestinal absorption of PSN was not significantly increased in duodenum, but obviously enhanced 3.62‐ and 13.1‐fold in jejunum and ileum, respectively. In particular, the in vivo pharmacokinetic results indicated that the oral bioavailability of probucol was greatly improved 8.97‐fold by PSN. Thereby, the high‐drug‐loading self‐assembled nanoemulsion was very effective in enhancing the oral absorption of high‐dosing poorly water‐soluble drugs. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:1301–1306, 2013